Sclerosing Xanthofibroma of the Rib That Mimics a Very Aggressive Malignant Tumor of the Thoracic Wall. (23rd September 2014) - Caushi, F.; Xhemalaj, D.; Bani, I.; Skenduli, I.; Gega, B.; Hafizi, H.; Mezini, A.
Abstract : Sclerosing xanthofibroma is a benign lesion generally of flat bones that is thought to be caused by a reactive response to intramedullary hemorrhage following chest wall trauma. We are reporting a case of a 56-year-old man that was complaining of a dump pain on the right back and a swelling right in this place for several weeks. The radiology was suggesting an aggressive malignant tumor of the chest wall and probably metastasis in both lungs meanwhile the patient was in good state and very active. The surgery was decisive for the diagnosis that, to the fortune of the patient, it was sclerosing xanthofibroma.